Malaria Prevalence and Distribution of Plasmodium Species in Southern Region of Ethiopia - Anmut Assemie (Journal of Parasitology Research)
Malaria is caused by Plasmodium species and transmitted by Anopheles mosquitoes, which is the most common medical concern all over the world, including in Ethiopia. The current systematic review’s goal was to determine the overall malaria prevalence and Plasmodium species distribution in Ethiopia’s southern area. To achieve these objectives, 716 articles were manually searched from online databases such as PubMed, Scopus, Google Scholar, Science Direct, and Web of Science. The pooled metalogistic regression was calculated with the STATA 16 software to present the pooled prevalence with a 95% confidence interval (CI). Eighteen full-text articles met the inclusion criteria and were included in the study, out of the 716 studies initially identified. The majority of the articles in the systematic review used a cross-sectional study design, with sample sizes ranging from 160 to 583,668 participants. The study’s lowest and highest malaria prevalence was 0.93% and 82.84%, respectively. During the current systematic review, the estimated malaria prevalence was 19.19% (95% CI: 14.67–23.70). There were 263,476 positive individuals in the study, accounting for 148,734, 106,946, and 7,796 cases of P. falciparum, P. vivax, and mixed infections, respectively. The overall prevalence of P. falciparum and P. vivax was 8.97% (95% CI: 6.31, 11.63) and 7.94% (95% CI: 6.56, 9.33), respectively. According to the systematic review, the most predominant Plasmodium species responsible for malaria disease in the study area was P. falciparum. The highest malaria rates were found in this systematic review. In the systematic review, P. falciparum was the most dominant Plasmodium species that was responsible for malaria disease in the study area. This systematic review indicates the highest malaria prevalence in the southern regions of Ethiopia. Therefore, existing malaria prevention and control strategies in the southern region of Ethiopia should be revised.